Discrepant effects of metal and metal oxide nanoparticles on anammox sludge properties: A comparison between Cu and CuO nanoparticles. (October 2018) - Zhang, Zheng-Zhe; Cheng, Ya-Fei; Xu, Lian-Zeng-Ji; Wu, Jing; Bai, Yu-Hui; Xu, Jia-Jia; Shi, Zhi-Jian; Jin, Ren-Cun
Graphical abstract: Highlights: Long-term effects of CuNPs and CuONPs on anammox sludge properties were compared. 5 mgCu L −1 CuNPs reduced the metabolic activity and abundance of anammox bacteria. 1–160 mgCu L −1 CuONPs had no adverse effects on reactor performance. The release of Cu(II) was well correlated with variations in sludge properties. Abstract: Metal and metal oxide nanoparticles (NPs) show differences in antimicrobial activity due to different chemical and physical properties. Using copper as a representative example, this study compared the NP effects on anaerobic ammonium oxidation (anammox) bacteria in wastewater treatment. Long-term exposure to 5 mgCu L −1 CuNPs reduced the physiological activity and abundance of anammox bacteria, thereby causing deterioration of reactor performance. However, anammox granules exhibited stronger resistance and resilience to perturbation by 1–160 mgCu L −1 CuONPs, and no adverse effects on performance were observed. Moreover, the level of Cu(II) released from NPs in the influent exhibited good correlations with variations of the community structure and sludge properties. Therefore, the effects of Cu-based NPs on anammox sludge properties are dependent on their forms and levels, and their discrepant effects are partially attributed to their ability to release ionic copper.